Understanding Learning Loss in Primary Schools: Blended Learning Policy - Suarlin, Suarlin; Elpisah, Elpisah; Raihan, Siti; Setiawan, Iwan (Journal of Educational Science and Technology (EST), 2024)
The implementation of blended learning, combining face-to-face and online methods, presents a potential solution for primary schools in the new normal era. However, concerns arise regarding its effectiveness, especially regarding potential learning loss among students. This study addresses this gap by investigating learning loss in Makassar City elementary schools utilizing a descriptive survey design. Among 314 randomly selected students, 56.37% reported experiencing learning loss, with causal factors including student readiness (63.28%), teacher readiness (25.06%), and facility readiness (11.6%). Categorization of learning loss levels revealed varying degrees, with 6.68% very high, 24.85% high, 40.11% moderate, 22.60% low, and 5.65% very low. Predominantly, learning loss was attributed to student readiness. However, teacher and facility readiness also played significant roles. Importantly, implementing blended learning with a pedagogical flow showed promise, with 43.63% of students reporting no learning loss. This research underscores the need for comprehensive strategies to address learning loss in blended learning environments, emphasizing student preparedness while also enhancing teacher and facility support. As educators navigate the challenges of the new normal, understanding, and mitigating learning loss are essential for ensuring effective educational outcomes.